(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3NHQ Bd GdegdH HbfOGHjd (B: (3bGdhG (B: (3hgQH Bd GdegdH HYjGdGJge Edi bfOGHjd , aMQbJ efGRdge HGdHUQI hgOeJ s
(3BNQgG (B:s
(3bGd CHh GdjbXGf (B: (3hef Hfi YHO GdOGQ Hfh LHjQ hdge HbjI bdjdI HGdHUQI Qhi Yfg fGaY , hdjS fHjg HCSf efg GfJgi GdLRA GdKGef , hjdjg GdLRA GdJGSY hChdg (B: (3Hfh YHO Hf bUi s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs